Molecular Docking and Pharmacokinetic Prediction of Potential Compounds from Luffa acutangula as Antidiabetic Candidates - Hasan, Rahmawaty; Herowati, Rina; Widodo, Gunawan Pamudji (PHARMACY: Jurnal Farmasi Indonesia (Pharmaceutical Journal of Indonesia), 2023)
Luffa acutangula is commonly used, but its considerable potential as an alternative treatment for diabetics with a molecular target action is not yet known. Preliminary study of bioinformatics to decipher the compounds of L. acutangulaable to interact with the protein targets of antidiabetic therapy. This study aims to identify the potential compounds of L. acutangula that are thought to interact with the insulin receptor, aldose reductase, and PTP-1B, as well as provide predictions of pharmacokinetics and toxicity. Molecular docking was conducted in AutoDock 4.2.6 with the stages initiated by the preparation of macromolecules (PDB ID: 1IR3; 2PEV; 4Y14) and ligands, molecular docking, and visualization. The pharmacokinetic profiles are predictable by using the Swiss ADME and toxicity estimates by Toxtree. The results showed that cucurbitacin B, cucurbitacin E, oleanolic acid, catechin, ferulic acid and apigenin are the most potential compounds to interact with the macromolecular with a binding energy response similar to the native ligand. Pharmacokinetic predictions show that cucurbitacin B and cucurbitacin E deviate from one Lipinski rule (BM> 500), do not diffuse into the blood brain barrier, are not CYP450 inhibitors, as well as classified as Pgp substrates. The prediction of toxicity indicates that all potential compounds are classified as high toxicity compounds with a risk of narcosis, except oleanolic acid and ferulic acid. These compounds are not genotoxic or non-genotoxic carcinogens.